Design and simulation of a gripper structure of cluster tomato based on manual picking behavior - Zheng, Yifeng; Pi, Jie; Guo, Tiezheng; Xu, Lei; Liu, Jun; Kong, Jie (Frontiers in Plant Science, 2022)
Picking robot technology plays an important role in the rapid promotion of precision agriculture. The development of a successful robot gripper is critical for the final promotion and industrialization of the tomato picking robot. This paper investigated the cluster tomato picking strategy and the gripper structure design based on this strategy to address the problem of poor adaptability of the existing gripper design in the cluster tomato picking scene. Starting from the research on the behavior of artificially picking cluster tomatoes, the grasping method, finger structure parameters and picking movement pattern of the human hand are analyzed. The evaluation criteria of the gripper are summarized, a simplified mathematical model of the gripper is established, and the picking strategy under the model of the gripper is proposed. Furthermore, according to the simplified gripper model, a rigid-flexible coupling gripper structure is designed, and the gripping simulation analysis is carried out. According to the simulation results, the gripper can smoothly grab medium and large tomatoes with diameter of 65∼95 mm. The peak force and fluctuation force of tomato with different sizes during grasping were less than the tomato’s minimum damage force. The gripper has adaptability and stability characteristics, providing technical support for gripper manufacturing and the construction of a picking system for a tomato picking robot.